POLICY IMPLEMENTATION MODEL FOR HANDLING CORONAVIRUS DISEASE 19 (COVID 19) BY STREET-LEVEL BUREAUCRATS (SLB) - Sakir, Mochammad; Wahyu Nurdiansyah Nurdin; Swastiani Dunggio (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Street-level bureaucrats are the spearhead of policy implementers, they have the power, autonomy and coping mechanisms that they carry out to produce final policies that may not be in accordance with policy demands. This study uses a qualitative approach to investigate the implementation model of the coronavirus disease 19 (Covid 19) handling policy by Street-Level Bureaucrats (SLB). The design used in this study is a case study. The results of the study show that in implementing the Covid 19 handling policy, not all street-level bureaucrats can understand the provisions for implementing the policy, even though SLB already has individual knowledge, skills, and expertise, as well as policy beliefs. Street-Level Bureaucrats (SLB) also take discretionary actions so that the services of policy implementing officers are in accordance with what the community expects, as well as coping actions because lower-level implementers are not balanced with the provision of adequate service facilities and resources . The form of coping carried out by lower-level implementing officers is in the form of rejecting Covid-19 patients because the treatment room is almost full or because the number of health workers is limited in serving Covid-19 patients in a hospital, or recommending Covid-19 patients to be referred to hospitals according to local government regulationsKeywords:coronavirus disease 19 (covid 19), policy implementation, street-level bureaucrats (SLB